Bowel obstruction from wild bananas: a neglected health problem in Laos. - Slesak, G; Mounlaphome, K; Inthalad, S; Phoutsavath, O; Mayxay, M; Newton, P (2011)
We investigated the significance and risk factors of bowel obstruction caused by the consumption of wild bananas (BOWB) in Laos. Of six patients with BOWB in Luang Namtha, North Laos, five required enterotomy for phytobezoars. All had eaten wild banana (WB) seeds. Of 227 other patients/relatives: 91.2% had eaten WB; 46.3% had also eaten the seeds and 45.4% knew of complications resulting from eating WB; 42.3% were aware of the complications of ingesting the seeds (constipation [37.9%], appendicitis/abdominal pain/vomiting [2.6% each] and bloated stomach/death [1.3% each]). Middle/highland Lao ethnicity was associated with WB and seed consumption (odds ratio [OR] 9.91 and 2.33), male sex with WB consumption and unawareness (OR 4.31 and 1.78). At all surgically-equipped hospitals in Laos, 33/44 doctors knew of BOWB, describing patients as young adults (16/30), male (24/30) and from middleland Lao (18/30). Countrywide, 46/48 patients with BOWB required laparotomy in 2009 (incidence 0.8/100,000). All consumed WB seeds. BOWB is widespread in Laos, especially among young middleland Lao men consuming WB seeds on an empty stomach.